From waste to worth: stability, bioaccessibility, and cellular antioxidant activity of microencapsulated red grape pomace phenolics - Lingua, Mariana Soledad; Sabatino, María Eugenia; Cuatrin, Alejandra; Salvucci, Emiliano; Blajman, Jesica; Boye Bosch, Roxana Beatriz; Wunderlin, Daniel Alberto; Baroni, María Verónica (Wiley, 2025)
BACKGROUND: Red grape pomace (RGP) is a recognized winery by-product due to its phenolic profile with valuable antioxidant power and beneficial health properties. Following the latest trends in food science and technology, this study valorizes the use of RGP to obtain a food ingredient rich in antioxidant phenolics. An integrated approach was proposed, investigating the production by spray drying of easy-to-handle microparticles, rich in stable compounds with antioxidant properties demonstrated after simulated digestion using in vitro assays and Caco-2 cells. The changes in microbiota composition after fermentation were also studied. RESULTS: Among investigated wall materials, maltodextrin/skimmed milk powder (1:1) 300 g L−1 offered the highest drying yield, appropriate moisture, solubility, and adequate microparticle morphology, as well as the best stability of polyphenols. Encapsulation improved the protection of phenolic compounds and the in vitro antioxidant capacity during 120 days of storage at 4 and 25 °C, as compared to those unencapsulated. Microencapsulated polyphenols bioaccessibility was evident in 15 out of 22 compounds initially quantified, with 6.6% potentially absorbed. The polyphenols from microcapsules modulated positively the microbial ecology after colonic fermentation. Those derived from intestinal digestion demonstrated the highest capacity to reduce the reactive oxygen species under oxidative stress conditions in Caco-2 cells. CONCLUSION: RGP could be used in the development of new food ingredients as a potential candidate for health promotion. This represents the first report on the benefits of RGP microcapsules as a food ingredient, validating its final biological effects in a cellular model considering the processing and digestion effects.